Mechanisms of disturbed emotion processing and social interaction in borderline personality disorder: state of knowledge and research agenda of the German Clinical Research Unit - Schmahl, Christian (Borderline Personal Disord Emot Dysregul, 2014)
The last two decades have seen a strong rise in empirical research in the mechanisms of emotion dysregulation in borderline personality disorder. Major findings comprise structural as well as functional alterations of brain regions involved in emotion processing, such as amygdala, insula, and prefrontal regions. In addition, more specific mechanisms of disturbed emotion regulation, e.g. related to pain and dissociation, have been identified. Most recently, social interaction problems and their underlying neurobiological mechanisms, e.g. disturbed trust or hypersensitivity to social rejection, have become a major focus of BPD research. This article covers the current state of knowledge and related relevant research goals. The first part presents a review of the literature. The second part delineates important open questions to be addressed in future studies. The third part describes the research agenda for a large German center grant focusing on mechanisms of emotion dysregulation in BPD.